Perl cookbook - Christiansen, Tom.; Torkington, Nathan (Sebastopol, Calif. : O'Reilly, 1998)
The Perl Cookbook is a comprehensive collection of problems, solutions, and practical examples for anyone programming in Perl. Topics range from beginner questions to techniques that even the most experienced of Perl programmers will learn from. More than just a collection of tips and tricks, the Perl Cookbook is the long-awaited companion volume to Programming Perl, filled with previously unpublished Perl arcana. The Perl Cookbook contains thousands upon thousands of examples ranging from brief one-liners to complete applications. Covered topic areas spread across nearly four hundred separate "recipes," including: Manipulation of strings, numbers, dates, arrays, and hashes Reading, writing, and updating text and binary files Pattern matching and text substitutions Subroutines, libraries, and modules References, data structures, objects, and classes Signals and exceptions Accessing text, hashes, and SQL databases Screen addressing, menus, and graphical applications Managing other processes Writing secure scripts Client-server programming Internet applications programming with mail, news, ftp, and telnet These recipes were rigorously reviewed by scores of the best minds inside and outside Perl, foremost of which was Larry Wall, the creator of Perl himself. The Perl Cookbook is written by Tom Christiansen, Perl evangelist and coauthor of the bestselling Programming Perl and Learning Perl ; and Nathan Torkington, Perl trainer and co-maintainer of the Perl Frequently Asked Questions list
Includes bibliographical references (pages xxvii-xxix) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Perl (Computer program language); Perl (Langage de programmation); COMPUTERS -- Programming Languages -- Perl; Perl (Computer program language); PERL; Perl (langage de programmation)